Peran Kepala Sekolah dalam Pengembangan Kurikulum PAI - Abd. Hadi Rohmani (Tafhim Al-'Ilmi, 2020)
In the world of education, the principal becomes one of the most important holders inthe success of an institution he leads. Therefore, in order to be an ideal institution, atruly competent school principal is needed, who knows the duties, functions andobligations as a school principal. Therefore, in this article, the role ofschool/madrasa principal will be discussed In developing PAI curriculum